Analisis Pengaruh Mobile Banking Terhadap Kinerja Teller Melayani Transaksi Studi Kasus (BSI KCP Medan Kampung Baru). - Nadya Ananda Efendi (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
The mobile technology advancement has been growth rapidly. Every persons use mobile phone to support their daily activities. This condition make banks have to change their traditional methods of customer service to adoption of information technology.Customers today require more personalized services at any time and any place. Mobilebanking is one of advanced information technologies that can employ to achieve a high level of customer services and emerging technology that permits conduct of banking transaction through mobile phone. For bank’s customers, this application will support their banking transaction if they think it has a usefulness and easy to use. The important one is customer trust to mobile banking application. This research purposes to test the effect of perceived usefulness, perceived ease of use and trust to use of mobile banking. A survey was conducted at BSI KCP Medan Kampung Baru Collected data analized with multiple regression analysis. The results of this research show that perceived usefulness, perceived ease of use and trust tend to have effect on use of mobile banking And There are still many customers who make transactions directly to the teller even though there is mobile banking.